PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) BERBANTUAN VIRTUAL REALITY (VR) TERHADAP KEMAMPUAN SPASIAL SISWA - Sarah, Siti; Armanto, Dian (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aimed to determine the effect of the Realistic Mathematics Education (RME) approach assisted by Virtual Reality (VR) on students’ spatial ability and to describe students’ answer processes related to spatial ability. This research employed a pre-experimental method with the one-group pretest-posttest design. The population consisted of all eighth-grade students of MTs Swasta Muhammadiyah Sei Apung Jaya, while class VIII-Amanah was selected as the sample using cluster random sampling. Data were collected through tests, questionnaires, and documentation. Based on the pretest results, the average score was 52.08 and increased to 84.62 in the posttest. The analysis showed that the data were normally distributed and linear, allowing hypothesis testing to be conducted. Simple linear regression analysis resulted in the equation Ŷ = 34.495 + 0.784X with a correlation coefficient of 0.926, indicating a strong relationship between variables X and Y. The coefficient of determination was 85.8%, meaning that the Realistic Mathematics Education (RME) approach assisted by Virtual Reality (VR) contributed 85.8% to students’ spatial ability. The t-test results showed that  (12.526 > 2.056) with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Furthermore, the use of VR helped students understand geometric concepts more concretely and interactively.